Concept of Children's Education According to Muhammad Nur Abdul Hafizh Suwaid (Study Of Book Analysis Manhaj At-Tarbiyah An-Nabawiyah Lit-Tifl) - M. Ma’ruf; Ira Misraya (Universitas Yudharta Pasuruan, 2020)
This study analyzed the thoughts of Muhammad Nur Abdul Hafizh Suwaid about the concept of child education in the Manhaj at-Tarbiyah an-Nabawiyah lit-Tifl book. This type of research uses literature. The results of this study found that the concept of child education according to Muhammad Suwaid divided it into three stages, namely, pre-birth education, post-birth education, education until adolescence. The relevance of the concept of child education to children’s education in the current era can be done through education in Indonesia, namely: religious spiritual strength, self-control, personality and skills. This means that education is not only fixated on one goal, such as intelligence, but is holistic with other goaals to shape the character or personality of Indonesian people as a whole.